Native Life in Travancore - Mateer, Samuel, (Brill | Manohar Publishers & Distributors, 2024)
Numerous writings have been written about the history of Kerala by many non-Indian scholars. From ancient times, Greeks, Jews, Syrians, Arabs, Turks, Persians, Portuguese, British, etc., have written extensively about the history and region of Kerala. The book is an attempt to write the history of Travancore State. It is a 25-year-old study based on classified documents written in Malayalam, Tamil, and English. It covers reports like Abstracts of Castes and Ceremonies and Statistical Topics of Legislation and Judicial Administration, Land Tenure, Taxation, and Revenue, etc., from where all the socioeconomic history is taken from. The book is an anthropological survey of southern Kerala, i.e. Travancore State, where castes of lower and upper origins, such as Pulayas, Ezhavas, Shanars, Nambudiris, and Royal Family of Travancore, are discussed in great detail. Also, it describes the practices and lives of Muslims and followers of Syriac Christianity. The author covers the lives of women, the role of missionaries in evangelizing the region, the economy, laws, and regulations. It also discusses the kinds of cash crops, followed by fisheries, music, and customs, the issue of slavery, the role of Christian missions, and Hindu customs and practices followed in the region. This book covers the cultural, regional, and socio-economic aspects of the Travancore region, which was a Princely state.